Ecological scenarios: Embracing ecological uncertainty in an era of global change - K. Clark‐Wolf; W. E. Moss; B. W. Miller; I. Rangwala; H. R. Sofaer; G. W. Schuurman; D. Magness; A. J. Symstad; J. D. Coop; D. B. Bachelet; J. J. Barsugli; A. Ciocco; et al. (Ecosphere)
Abstract Scenarios, or plausible characterizations of the future, can help natural resource stewards plan and act under uncertainty. Current methods for developing scenarios for climate change adaptation planning are often focused on exploring uncertainties in future climate, but new approaches are needed to better represent uncertainties in ecological responses. Scenarios that characterize how ecological changes may unfold in response to climate and describe divergent and surprising ecological outcomes can help natural resource stewards recognize signs of nascent ecological transformation and identify opportunities to intervene. Here, we offer principles and approaches for more fully integrating ecological uncertainties into the development of future scenarios. We provide examples of how specific qualitative and quantitative methods can be used to explore variation in ecological responses to a given climate future. We further highlight opportunities for ecological researchers to generate actionable projections that capture uncertainty in both climatic and ecological change in meaningful and manageable ways to support climate change adaptation decision making.